Sex-chromosome recombination in common frogs brings water to the fountain-of-youth - Rodrigues, Nicolas; Studer, Tania (Molecular biology and evolution, 2018)
Abstract. According to the canonical model of sex-chromosome evolution, the degeneration of Y or W chromosomes (as observed in mammals and birds, respectively)
Ursprünglich falsch zitiert als: Molecular Biology and Evolution, Volume 35, Issue 4, 1 April 2017
Gesehen am 14.04.2020